Nitrogen loss by anaerobic ammonium oxidation in unconfined aquifer soils - Wang, Shanyun (Sci Rep, 2017)
Anaerobic ammonium oxidation (anammox) is recognized as an important process for nitrogen cycling, yet little is known about its role in the subsurface biosphere. In this study, we investigated the presence, abundance, and role of anammox bacteria in upland soil cores from Tianjin, China (20 m depth) and Basel, Switzerland (10 m depth), using isotope-tracing techniques, (q)PCR assays, and 16 S rRNA & hzsB gene clone libraries, along with nutrient profiles of soil core samples. Anammox in the phreatic (water-saturated) zone contributed to 37.5–67.6% of the N-loss (up to 0.675 gN m(−2 )d(−1)), with anammox activities of 0.005–0.74 nmolN g(−1 )soil h(−1), which were even higher than the denitrification rates. By contrast, no significant anammox was measured in the vadose zone. Higher anammox bacterial cell densities were observed (0.75–1.4 × 10(7 )copies g(−1 )soil) in the phreatic zone, where ammonia-oxidizing bacteria (AOB) maybe the major source of nitrite for anammox bacteria. The anammox bacterial cells in soils of the vadose zone were all <10(3 )copies g(−1 )soil. We suggest that the subsurface provides a favorable niche for anammox bacteria whose contribution to N cycling and groundwater nitrate removal seems considerably larger than previously known.